Perbandingan Estimasi Anggaran Biaya Antara Metode BOW, SNI Dan Perhitungan Kontraktor - Bambang Piluto (Universitas Islam Lamongan, 2020)
In determining the price of a job, it need the basic tool of unit price analysis, namely the construction costs analysis. In calculating the construction costs analysis there are several methods have been generally used such as analysis of BOW, SNI and also companies that make their own calculation analysis. A comparative study is needed from the three methods so that it can be seen which is more effective and efficient as a basis for all parties in determining the strategy in terms of cost budget estimates. The study was conducted by preparing a project cost budget plan based on the volume of works on the bill of quantity (BoQ). The unit price analysis is calculated based on BOW analysis, SNI analysis and Contractor version analysis. From the estimation results, a price based on BOW analysis is IDR 2,682,315,013,-, based on SNI analysis is IDR 1,958,002,381, - and based on analysis of contractor calculations is IDR 1,781,956,483. Differences in price between BOW and SNI is IDR 724,312,632. Differences in price between BOW and contractors calculation is IDR 900,358,529. Differences price between SNI and contractors calculation is IDR 176,045,897.